1997
DOI: 10.1557/jmr.1997.0095
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of quenched melt-textured YBa2Cu3O7−δ materials

Abstract: The microstructure of YBa2Cu3O7−δ (YBCO) materials, melt-textured in air and quenched from the temperature range 900–;990 °C, has been characterized using a combination of x-ray diffractometry, optical microscopy, scanning electron microscopy, transmission electron microscopy, and energy dispersive x-ray spectrometry. BaCu2O2 and BaCuO2 were found to coexist in samples quenched from the temperature range 920–960 °C. The formation of BaCu2O2 preceded the formation of YBCO. Once the YBCO had formed, BaCu2O2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Previous results on stoichiometric Y123 samples [3] showed that the melt quenched from 990 • C consisted solely of BC1 and CuO and that BC2 formed on samples quenched from 960 • C and lower temperatures (before Y123 formation). Therefore, there must be a region of stability of BC2 in air at some temperature below 990 • C. In the case of samples of Y123+20 mol% Y211 only a peak in the volume fraction of BC1 is observed at approximately 995 • C (see table 3).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous results on stoichiometric Y123 samples [3] showed that the melt quenched from 990 • C consisted solely of BC1 and CuO and that BC2 formed on samples quenched from 960 • C and lower temperatures (before Y123 formation). Therefore, there must be a region of stability of BC2 in air at some temperature below 990 • C. In the case of samples of Y123+20 mol% Y211 only a peak in the volume fraction of BC1 is observed at approximately 995 • C (see table 3).…”
Section: Discussionmentioning
confidence: 89%
“…Samples are produced using techniques described elsewhere [3,4]. Briefly, precursor powders of Y123 and Y211 are produced by co-precipitation and calcined separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure of the type II regions also shows that they are formed from stoichiometric Y123 particles. The large, segregated regions of BC1 and BC2, characteristic of Type II regions, are also observed in stoichiometric Y123 samples that have been quenched above the Y123 solidification temperature [16]. The large, blocky Y211 particles observed in type II regions are also present in pure Y123 samples [17] and are very different to the morphology and size of the Y211 particles present in samples with CeO 2 or Y 2 O 3 additions [18].…”
Section: Y211 Low Concentration Regionsmentioning
confidence: 91%
“…They are 31, 39 and 54 K/J·m for the systems (II), (I) and (III), respectively. [8,10]. However, during the investigation of the microstructure of the tempered samples, the formation of the YBa 2 Cu 3 O 7-δ compound was found to be not on the border between the grain surfaces and the solution-melt, but rather in the ellipsoid regions of the crystallized solution-melt ( fig.4).…”
Section: Introductionmentioning
confidence: 98%